2012
DOI: 10.1258/jrsm.2012.120009
|View full text |Cite
|
Sign up to set email alerts
|

Weekend hospitalization and additional risk of death: An analysis of inpatient data

Abstract: Admission at the weekend is associated with increased risk of subsequent death within 30 days of admission. The likelihood of death actually occurring is less on a weekend day than on a mid-week day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
284
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(307 citation statements)
references
References 11 publications
15
284
4
4
Order By: Relevance
“…Again, IHM rate was higher when admission occurred in post-office hours [8] and during the holidays [19] . As for WE versus WD, although a high mortality in subjects admitted during the WE has been reported by several authors, with an estimated increase of risk between 10% and 32% [14,15,[20][21][22] , in our study there was a trend in which more patients admitted during the WE died than those admitted on WD, but this was not confirmed by multivariate analysis. The results reported in the literature are not always consistent when considering the levels of hospital: the prognostic value of WE admission was identified more frequently in major teaching hospitals compared with nonteaching hospitals [23] , but no correlation between WE admission and IHM was found in patients admitted to tertiary care hospitals [24] .…”
Section: Discussioncontrasting
confidence: 87%
“…Again, IHM rate was higher when admission occurred in post-office hours [8] and during the holidays [19] . As for WE versus WD, although a high mortality in subjects admitted during the WE has been reported by several authors, with an estimated increase of risk between 10% and 32% [14,15,[20][21][22] , in our study there was a trend in which more patients admitted during the WE died than those admitted on WD, but this was not confirmed by multivariate analysis. The results reported in the literature are not always consistent when considering the levels of hospital: the prognostic value of WE admission was identified more frequently in major teaching hospitals compared with nonteaching hospitals [23] , but no correlation between WE admission and IHM was found in patients admitted to tertiary care hospitals [24] .…”
Section: Discussioncontrasting
confidence: 87%
“…We used the risk-adjusted figures reported in the published studies that have been cited as support for the 7-day services initiative. We applied the inverse of the risk-adjusted odds ratios reported by Freemantle et al 3 and by Aylin et al 15 to the odds [p/(1 -p)] of mortality at weekends observed in our data. This represents the expected odds of mortality if weekend patients experienced the same death rate as those admitted during the week once we control for their risk characteristics.…”
Section: Study 1: Estimating the Potential Costs And Benefits Of Intrmentioning
confidence: 99%
“…[1][2][3][4] Although there is evidence for this phenomenon in all out-of-hours periods -principally at night and at weekends -it has become known as the 'weekend effect' because the seminal studies in this area concentrated on weekend admissions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations